An Evaluation of the Measurement Properties of the Five Cs Model of Positive Youth Development - Conway, Ronan J.; Heary, Caroline; Hogan, Michael J. (Frontiers in Psychology, 2015)
There is growing recognition of the need to develop acceptable measures of adolescent’s positive attributes in diverse contexts. The current study evaluated the measurement properties of the Five Cs model of Positive Youth Development (PYD) scale (Lerner et al., 2005) using a sample of 672 Irish adolescents. Confirmatory factor analyses indicated that a five-factor model provided a good fit to the data. The internal reliability and construct validity of the Five Cs model were supported, with character the strongest predictor of contribution, while connection was the strongest predictor of risky-behaviours. Notably, confidence was significantly negatively related to contribution, and positively related to risky-behaviours. Multi-group hierarchical nested models supported measurement invariance across early- (11-14 years) and late- (15-19 years) adolescent age groups, with partial invariance found across gender. Younger adolescents evinced higher PYD, while PYD was associated with higher contribution and lower depression and risk-behaviours across all groups. The application of the PYD framework as a measure of positive functioning across adolescence is discussed.